2019
DOI: 10.1182/blood-2019-125623
|View full text |Cite
|
Sign up to set email alerts
|

CPX-351 Induces Deep Response and Suppress the Impact of Poor Prognosis Mutations (TP53, ASXL1, RUNX1 and EVI1) Defined By ELN-2017 in t-AML and MRC AML: A Report from a Multicentric French Cohort

Abstract: Introduction CPX-351 is a liposomal formulation of cytarabine and daunorubicin packaged at a 5:1 molar ratio. This drug has recently been approved by FDA and EMEA for patients with therapy-related acute myeloid leukemia (t-AML) or AML with myelodysplasia-related changes (MRC-AML). The primary objective of this study was to analyze the efficacy of CPX-351 in a real-life setting, evaluating the impact of mutations on response and minimal residual disease (MRD) in responding patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Interestingly even the presence of TP53 mutation in the context of a complex karyotype did not impact on the CR rate. This is in contrast with a previous paper showing the detrimental influence of TP53 mutations on CR/CRi rate in patients treated with CPX-351 induction 26 , but consistent with more recent data from a French Group 27 , thus suggesting the need of further studies in this setting. In addition, CR rate was not lower among patients progressed under hypomethylating therapy for MDS.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly even the presence of TP53 mutation in the context of a complex karyotype did not impact on the CR rate. This is in contrast with a previous paper showing the detrimental influence of TP53 mutations on CR/CRi rate in patients treated with CPX-351 induction 26 , but consistent with more recent data from a French Group 27 , thus suggesting the need of further studies in this setting. In addition, CR rate was not lower among patients progressed under hypomethylating therapy for MDS.…”
Section: Discussionsupporting
confidence: 85%
“…There have been no prospective, randomized trials comparing intensive with non-intensive therapies for patients with mTP53-AML and thus it is only feasible to use indirect comparisons using historical data at present. As previously-discussed, older patients with mTP53-AML treated with classical induction therapy including CPX-351 are predicted to only have a CR/CRi rate of 30-40% and median OS of only about 6-7 months [6,11,33,99]. Less-intensive options such as HMA + venetoclax are associated with CR/CRi rates of about 55-65% in mTP53-AML and this favorably, although indirectly, compares with intensive therapy [10,15,61].…”
Section: Intensive Vs Less-intensive Inductionmentioning
confidence: 84%
“…At the ASH 2018, the results from the Italian compassionate use of CPX-351 have been reported: CR was observed in 86.3% of the 75 enrolled patients, with 45% of them who achieved also the MRD-negativity after the first cycle [ 16 ]. Interestingly, during the same meeting other groups reported that patients receiving CPX-351 achieved a 100% of response if IDH2-mutated [ 17 ], and Chiche et al assessed that the favorable outcome was observed in patients after HSCT and CPX-351 erased the poor prognosis associated with unfavorable mutations [ 18 ], thus making CPX-351 an attracting therapeutic chance for this subgroup of AML patients.…”
Section: Discussionmentioning
confidence: 99%